DOMINANT FACTORS STUDY OF COLIFORM BACTERIA CONTAMINATION IN SHALLOW GROUNDWATER AT YOGYAKARTA CITY (CASE STUDY: TAHUNAN AND PRINGGOKUSUMAN) - Kalyana Putri, Enda
The use of shallow groundwater as a source of clean water is still being the preferred choice for Yogyakarta society because of its relatively easy, cheap, and practical use. However, on-site Domestic Wastewater Management System that widely used by residents was less than ideal due to limited land in densely populated areas. So, it potentially contaminates residents' wells. This research was conducted in Tahunan and Pringgokusuman which were expected to represent the condition of shallow groundwater pollution in Yogyakarta City. The purpose of this study were to identify the spread of Coliform bacterial contamination, examine the dominant factors causing coliform bacterial contamination in shallow groundwater, and provide suggestions for its management. The value of groundwater quality parameter Total Coliform was used as an independent variable, while the dependent variables were used depth, type, and wall of well, type of SPALD, distance of well to septic tank, latrine, and other pollutant sources, population density, land use, groundwater level, rainfall, soil type, and slope. Those parameters were analyzed statistically with logistic regression using IBM SPSS 26 software and supported by the results of the Analytical Hierarchy Process (AHP) study using Expert Choice software. Meanwhile, mapping of coliform bacterial contamination in shallow groundwater would be processed using ArcGIS 16.2 software. The results showed that 83,3% of the shallow groundwater samples in the study area did not meet the total coliform standards for clean water. While the dominant factors that most influence the bacteriological quality of groundwater in the Total Coliform parameter were the distance of other pollutant sources to the well, slope, and the distance of the septic tank to the well. Suggested groundwater management are through technological, institutional, and social approaches.